Utilization of Inferior Green Coffee Bean Oil for Air Freshener Gel - S. Rosalinda; Nadyah Rachma Dewi; Sarifah Nurjanah (The University of Lampung, 2022)
More than 20% of the coffee beans harvested are not traded because they do not pass the sorting. Coffee beans that do not pass the sorting are referred to as inferior green coffee beans (inferior coffee).. The purpose of this study was to determine the combination of inferior coffee oil concentration and gel material that gave the best characteristics as air freshener. This research method is a laboratory experimental method with descriptive analysis. The research stages consisted of preparation of materials and equipment, extraction of inferior coffee with the soxhletation method and making air freshener. The concentration of inferior coffee oil used was control (A0) 1%; (A1); 2% (A2); 4% (A3) and each concentration was added to a formulation consisting of 0.75 grams of carrageenan, 0.5 grams of agar, 0.25 grams of pectin, 0.05 grams of sodium benzoate, 5 grams of propylene glycol and aquadest to adjust the amount to 50 grams. Product testing parameters consist of strength test, gel hardness test, gel stability test, preference test, liquid evaporation test and fragrance resistance test. The results showed that the best air freshener with 4% coffee oil concentration resulted in a gel strength of 482 g/cm2; gel hardness test 1064 g/cm2; gel stability test 2.387%; preference test 2.78; evaporation test is 69.632% and the value of fragrance resistance is 3.003. Keyword: soxhletation, air freshener gel, inferior coffee oil, gel material, extraction